2014
DOI: 10.1007/s13762-013-0473-z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of load mass on real-world PM1 mass and number emissions from a heavy-duty diesel bus

Abstract: On-road emission profiles of ultra-fine particle matter with aerodynamic diameter \1 lm (PM 1 ) were obtained from a Euro IV diesel bus in Beijing under two typical load mass conditions. PM 1 mass and number emissions were recorded second by second using an electrical low-pressure impactor (ELPI). An on-road driving mode binning method was applied to relate instantaneous emission rate with real-time on-road driving conditions, and an engine-operating mode binning method was used to explore the impacts of engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…When comparing specific SPN 23 emissions (#/kWh) calculated according to the approach described in the "Evaluation Methodology" Section 2.5, it can be noticed that at higher load they were 75% more. This finding is in agreement with previous studies that observed increased particulate mass [20] and particle number emissions [21] for higher loads of a heavy-duty diesel truck and bus, respectively. SPN 10 emissions were 25% higher than SPN 23 at 10% payload and 20% at 55% payload.…”
Section: Effect Of Payloadsupporting
confidence: 94%
“…When comparing specific SPN 23 emissions (#/kWh) calculated according to the approach described in the "Evaluation Methodology" Section 2.5, it can be noticed that at higher load they were 75% more. This finding is in agreement with previous studies that observed increased particulate mass [20] and particle number emissions [21] for higher loads of a heavy-duty diesel truck and bus, respectively. SPN 10 emissions were 25% higher than SPN 23 at 10% payload and 20% at 55% payload.…”
Section: Effect Of Payloadsupporting
confidence: 94%
“…Overflow of citizens in cities is the main problem which causes higher level of air, particle, noise and light pollution (Dyr et al, 2019). All these and other reasons may do harm to environment and human health(C. Wang et al, 2015), (Tong et al, 2000), (Smieszek et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Emissions from motor vehicles are a major source of urban air pollutant emissions, such as nitric oxides, carbon monoxide, hydrocarbons, and carbon dioxide [1][2][3][4][5]. For instance, relevant research studies indicated that about 45% of the pollutant emissions in the United States were a direct consequence of vehicle operations [6].…”
Section: Introductionmentioning
confidence: 99%